Bacterial community diversity and potential eco-physiological roles in toxigenic blooms composed of Microcystis, Aphanizomenon or Planktothrix - Mankiewicz-Boczek, Joanna; Font-Nájera, Arnoldo; Gin, Karina Yew-Hoong; Graham, Jennifer L.; Strapagiel, Dominik; Gorney, Rebecca M.; Kok, Jerome Wai Kit; Te, Shu Harn; Kluska, Magdalena; Skóra, Milena; Seweryn, Michał; López-Hun, Francisco (Frontiers in Microbiology, 2025)
Cyanobacterial toxicity, cyanotoxins, and their impact on aquatic ecosystems and human health are well documented. In comparison, less is known about bloom-associated bacterial communities. Co-occurring bacteria can influence bloom development, physiology and collapse, and may also provide a niche for pathogenic bacteria. Existing research focuses on the cyanosphere of Microcystis-dominated blooms, despite the increasing prevalence of filamentous genera (Aphanizomenon and Planktothrix). This pilot study aimed to broaden our understanding of the bacterial consortia attached to morphologically distinct cyanobacteria (coccoid and filamentous) dominating phytoplankton communities and to explore their potential roles in amplifying the impacts of cyanobacterial blooms. We investigated four shallow freshwater bodies across three continents and two climate zones: an urban pond in the USA, a dammed reservoir and a natural lake in Poland, and an urban water body in Singapore. Amplicon sequencing (16S rRNA gene) was used to characterize bacterial communities, while shotgun metagenomics identified nitrogen- and phosphorus-cycling genes to infer potential eco-physiological functions. Cyanobacteria dominated bacterioplankton assemblages at all sites (>35.6%), with bloom composition influencing toxigenic profiles. A mixed bloom of Microcystis, Snowella, and Aphanizomenon had the broadest range of cyanotoxin synthetase genes (mcyE, cyrJ, anaF and sxtA). Microcystis blooms correlated with increased Roseomonas, while Planktothrix co-occurred with Flavobacterium – both bacteria likely contribute to nutrient-cycling within blooms and represent potential opportunistic pathogens for aquatic organisms and humans. The Microcystis cyanosphere exhibited the highest number of significant positive correlations with bacteria (19 relations), compared to Planktothrix and Aphanizomenon (11 and 2 relations, respectively). Non-diazotrophic blooms of Microcystis and Planktothrix showed greater abundances of nitrogen – (ureB, glnA, narB, and narHZ) and phosphorus-cycling genes (phoBHPR and ppk1), indicating a strong dependence on associated bacteria for nutrient acquisition compared to diazotrophic Aphanizomenon. These findings suggest that Aphanizomenon-dominated blooms may be sustained by simpler microbiomes. Our results provide preliminary evidence of cyanosphere heterogeneity potentially shaped by the dominance or coexistence of three morphologically and eco-physiologically distinct genera of cyanobacteria. A comprehensive knowledge of the taxonomy and functional roles of bloom-associated microbiomes is therefore essential to understand bloom activity, evaluate the environmental threat, and develop effective strategies for prevention and mitigation.